ESTIMATION OF INFORMATIVE VALUE OF ANTHROPOMETRIC PARAMETERS AND PREGNANCY COMPLICATIONS TO PREDICT PREECLAMPSIA - Индира Венеровна Сахаутдинова; Ирина Вениаминовна Герасимова (The Publishing House Medicine and Enlightenment, 2022)
The aim of the research - the aim of the study was to evaluate the effectiveness of the analysis of the anthropometric parameters of patients, overall weight gain and edematous syndrome as predictors of preeclampsia. Materials and methods. We conducted a randomized retrospective study. Group I included 34 patients with preeclampsia, group II included 66 patients, pregnancy, childbirth and the postpartum period were not complicated by hypertensive disorders. We analyzed the anthropometric parameters of patients at 12-14 weeks of gestation, as well as edematous syndrome at 30 weeks and overall weight gain in this period. Results. In the group of patients with late preeclampsia, BMI is close to the upper limit of normal. In the group of patients with early preeclampsia, a combination of edematous syndrome with low weight gain was noted. Conclusion. We recommend that at the stage of preconception preparation it is required to bring the BMI parameters to the average acceptable ones. The edematous syndrome should be considered as a predictor of preeclampsia. The combination of edematous syndrome and low weight gain should be regarded as a predictor of preeclampsia.